2019
DOI: 10.1080/19476337.2019.1674924
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tallow replacement by oat β-glucan and canola oil on the fatty acid and volatile compound profiles of low-fat beef burgers

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles Influence of tallow replacement by oat β-glucan and canola oil on the fatty acid and volatile compound profiles of low-fat beef burgers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…They found that in the samples where the back fat was replaced by the canola oil emulsion or canola oil and pineapple by-products, the fatty acid profile was improved (higher content of MUFA and PUFA and lower content of SFA) with respect to the control sample. Similarly, Szpicer et al [ 44 ] mentioned that in beef burgers where the tallow was partially replaced by canola oil or a mix of canola oil and β-glucan, the oleic, linoleic, and linolenic acids content increased with respect to control samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that in the samples where the back fat was replaced by the canola oil emulsion or canola oil and pineapple by-products, the fatty acid profile was improved (higher content of MUFA and PUFA and lower content of SFA) with respect to the control sample. Similarly, Szpicer et al [ 44 ] mentioned that in beef burgers where the tallow was partially replaced by canola oil or a mix of canola oil and β-glucan, the oleic, linoleic, and linolenic acids content increased with respect to control samples.…”
Section: Resultsmentioning
confidence: 99%
“…This result is considerably beneficial because a PUFA/SFA ratio lower than 0.45 may increase the incidence of cardiovascular diseases [ 6 , 46 ]. The use of gelled emulsion to replace animal fat in several meat products is a great strategy to improve several nutritional indices, including n-6/n-3 and PUFA/SFA ratios, as has been reported by several authors [ 9 , 11 , 41 , 44 ]. The partial substitution of pork backfat resulted in a decrease ( p < 0.05) of the atherogenicity (AI) and thrombogenicity (TI) indices; in all formulations, values less than 1 were found, which indicates that the formulations contribute to reducing the risk and severity of diseases [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of health, this is important because it indicates that the intake of fatty acids present in moriche fruits can have a protective effect, preventing the formation of blood thrombi and helping to prevent arteriosclerosis and cardiovascular disorders. In addition to the above, Méndez-Cid et al [ 15 ] and Szpicer et al [ 14 ] indicate that products made with vegetable fats rich in polyunsaturated fatty acids, such as canola oil, have low AI and TI values and high h/H values compared to animal fats such as beef tallow and tocino .…”
Section: Resultsmentioning
confidence: 99%
“…The identified fatty acids were compared with a standard according to their retention time in each respective chromatogram and are expressed as percentages. To calculate the nutritional quality and health indices, the equations reported by Szpicer et al [ 14 ] were used: …”
Section: Methodsmentioning
confidence: 99%
“…The basic composition of beef burgers (water, protein, fat and ash content) was determined by accredited FT-NIR nearinfrared laboratory (Polish Centre for Accreditation -Accreditation No. AB 1670) according to the method presented in the work of Szpicer et al (2019). Büchi nearinfrared spectrometer NIRFlex N-500 (Büchi Labortechnik AG, Switzerland) with NIRFlex Solids module in the spectral range of 12.500-4.000 cm 1 in reflectance mode and application Büchi Art.…”
Section: Near-infrared Spectroscopy Analysis (Nir)mentioning
confidence: 99%